Representasi Kasih Sayang Representasi Kasih Sayang Ayah Disabilitas melalui Gestur dan Ekspresi (Analisis Semiotika Roland Barthes pada Film Miracle In Cell No.7 Indonesia) - Eneng Agustina; Koesworo Setiawan; Robby Firliandoko (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2026)
The development of family communication demonstrates the importance of nonverbal communication in building emotional closeness. The Indonesian version of the film Miracle in Cell No. 7 depicts the affection of a father with a disability to his child through gestures and facial expressions. This study aims to analyze the delivery of affection through gestures and expressions. The method used is a descriptive approach and Roland Barthes' semiotic analysis. Data were obtained through observation, documentation, interviews, and literature studies. The results show that affective gestures, caring expressions, and a combination of both are the main signs representing protection, warmth, sincerity, and responsibility of a father. Connotatively, these meanings strengthen father-child closeness, while at the mythical level, this film challenges stereotypes about fathers with disabilities. Thus, nonverbal communication becomes the main means of displaying sincere fatherly affection in the family. Keywords: gesture, facial expression, disabled father, affection, Roland Barthes' semiotics.